2013
DOI: 10.4338/aci-2012-09-ra-0033
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of success for electronic health record implementation in small physician practices

Abstract: SummaryBackground: The federal government is promoting adoption of electronic health records (EHRs) through financial incentives for EHR use and implementation support provided by regional extension centers. Small practices have been slow to adopt EHRs. Objectives: Our objective was to measure time to EHR implementation and identify factors associated with successful implementation in small practices receiving financial incentives and implementation support. This study is unique in exploiting quantitative impl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…12 A survey of 544 small practices by Ancker et al found EHR implementation success to be associated with practices that treated fewer Medicaid and uninsured patients. 13 …”
Section: Discussionmentioning
confidence: 99%
“…12 A survey of 544 small practices by Ancker et al found EHR implementation success to be associated with practices that treated fewer Medicaid and uninsured patients. 13 …”
Section: Discussionmentioning
confidence: 99%
“…This could be the result of better preparation through the use of clinical champions, better organizational buy-in, effective leadership and change management and ultimate commitment to information technology that contribute to an ED's response to EHR implementation. 3638 Qualitative methods may be well suited to better understanding why facilities respond the way they do and how they can affect workflow delivered in a healthcare setting. 27,39 By mitigating inefficiencies gained by implementing EHRs, we may enhance the overall benefit of an electronic record and the subsequent value delivered to the patient and the healthcare system.…”
Section: Discussionmentioning
confidence: 99%
“…12,13,18,19 For example, a study by Ancker and colleagues found that in interviews with PCIP providers, positive attitudes about EHRs correlated with successful EHR implementation. 12 Our findings suggest that once an EHR is in place, prior comfort with computers and attitudes about the EHR do not predict future use of that EHR. These findings differ from findings of EHR adoption studies and may signify that once providers have overcome the hurdle of adopting an EHR, their attitudes about it do not affect their future use of EHR functions.…”
Section: Discussionmentioning
confidence: 99%
“…1215 However, to our knowledge, there is no evidence on whether comfort with technology and more positive attitudes about EHRs prior to implementation affect use of EHRs once they are implemented. We hypothesize that providers who are comfortable using computers and who feel optimistic about their potential effects on patient care might use more features of the EHR.…”
Section: Introductionmentioning
confidence: 99%